2016
DOI: 10.1590/1678-4324-2016160470
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Fitting Methods Applied for Thin-Layer Drying of Cape Gooseberry Fruits

Abstract: Drying data of cape gooseberry was used to compare two fitting methods: namely 2-step and 1-step methods. Literature data was also used to confirm the results. To demonstrate the applicability of these methods, two primary models (Page, Two-term-exponential) were selected. Linear equation was used as secondary model. As well-known from the previous modelling studies on drying, 2-step method required at least two regressions: One is primary model and one is secondary (if you have only one environmental conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The moisture ratio (MR) of samples was calculated using the following equation: MR=MtMeMiMe where MR is the moisture ratio; M t is the moisture content of the material at (any time kg water/kg dry solid); M i is the initial moisture content of the material before drying (any time kg water/kg dry solid); and M e is the equilibrium moisture content of tomato sample (any time kg water/kg dry solid). The equilibrium moisture content ( M e ) was assumed to be zero for drying since M e is relatively small compared to M t and M i and accepted to be negligible (Doymaz, ; Karacabey, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture ratio (MR) of samples was calculated using the following equation: MR=MtMeMiMe where MR is the moisture ratio; M t is the moisture content of the material at (any time kg water/kg dry solid); M i is the initial moisture content of the material before drying (any time kg water/kg dry solid); and M e is the equilibrium moisture content of tomato sample (any time kg water/kg dry solid). The equilibrium moisture content ( M e ) was assumed to be zero for drying since M e is relatively small compared to M t and M i and accepted to be negligible (Doymaz, ; Karacabey, ).…”
Section: Methodsmentioning
confidence: 99%
“…and M e is the equilibrium moisture content of tomato sample (any time kg water/kg dry solid). The equilibrium moisture content (M e ) was assumed to be zero for drying since M e is relatively small compared to M t and M i and accepted to be negligible (Doymaz, 2004;Karacabey, 2016).…”
Section: Mathematical Modelling 241 | Drying Kinetic and Model Asmentioning
confidence: 99%
“…where, M t , M o , and M e represents moisture levels in leaves at time interval of t, initial and equilibrium, respectively. This equation for moisture ratio was further modified to M t /M o by some researchers for ease in calculations as described in the literature (Al-Harahsheh et al, 2009;Doymaz, 2005;Karacabey, 2016). Besides, the most important aspect of drying process is mathematical modelling that may help to design drying equipment with optimum drying of desired product.…”
Section: Moisture Ratiomentioning
confidence: 99%
“…ANOVA also showed that the lack of fit was not significant for all response surface models, at 95% confidence level. This paper presents an evaluation of two fitting methods applied for thin layer drying of Capegooseberry (Erkan, 2016).…”
Section: The Dryer Is Simple In Construction At a Low Cost With Locmentioning
confidence: 99%
“…ANOVA also showed that the lack of fit was not significant for all response surface models, at 95% confidence level. This paper presents an evaluation of two fitting methods applied for thin layer drying of Capegooseberry (Erkan, 2016).Many studies have been reported on solar drying of various products (Fernando et al 2015, Xiaroran et al 2015.Out of the literature survey conducted, it is observed that tunnel dryers were not employed so far the studies on drying beef. Response surface methodology is also powerful to analyze the performance characteristics of the system.…”
mentioning
confidence: 99%